Estudo da expressão de lipase BTL2 de Bacillus thermocatenulatus em E. coli recombinante - Escallón, Ana María Vélez (2009)
Using recombinant DNA techniques, the lipase BTL2 gene of Bacillus thermocatenulatus was cloned in E. coli BL321 under control of the strong temperature-inducible λPL promoter. It was investigated, initially, in this work, the influence of different variables in cell growth and expression of lipase BTL2 by recombinant E. coli, through experiments performed in agitated flasks with LB medium. First, it was studied the influence of temperature of growth (between 27 ° C and 34.2 °C) and heat shock temperature (between 37.8 °C and 46.2 °C) in the expression of lipase BTL2 by E. coli recombinant, using statistical design of experiments. The results of this study, where the shock was performed in the early exponential phase, indicated as the best Tcresc = 27 °C and Tchoque = 45 °C, yielding cellular concentration of 0.6 g dry weight / L and enzyme activity of 121.000 U/g.wet.cel. Then, it was investigated the influence of the growth phase of the microorganism at the shock, through cultures with Tcresc = 27 °C and Tchoque = 45 °C, the results of these experiments showed how heat shock condition at the end of exponential phase, resulting in activity of 258.000 U/g.wet.cel It investigated the influence of different initial concentrations of glucose in the medium on cell growth and expression of the enzyme. The best results were obtained from cell mass with 10 g/L glucose and μmax = 0,16 h-1, Yx/s = 0,19 g/g, resulting in 1.2 g / L dry cel, enzymatic activity of about 250.000 U / g.wet.cel. Lower concentrations of glucose and higher concentrations led to smaller cell, but did not affect enzyme activity in the final. Based on previous cultures of E.coli were conducted simulations to calculate the best condition for feed-batch. The experimental test was performed with 10 g/L glucose at the beginning of cultivation, Tcresc = 30 °C, Tchoque = 45 °C. In this test, we were able to achieve 15 g/L dry.cel μmax = 0,38 h-1 with enzyme activity of 231.000 U/g.wet.cel, with resulting in 100 times more enzyme in this test than in cultivation in shaker in the best condition. The results of the simulation, obtained using model of Monod, predicted quite well those obtained experimentally. There was no significant accumulation of organic acids and all aminoacids consumed by the moment of shock. From the heat shock, those who were not exhausted with concentration remained constant. The enzyme produced in the test batch was recovered by breaking the cells in a French press to obtain with this methodology 272.000 U/g wet cells, whereas the results of the samples, which were disrupted by sonication resulted in much lower value. Was then investigated the efficiency of the protocol of sonication that was being used, by subjecting the cells to successive rounds of sonication. The results showed that actually the first cycle only 50% of the enzyme was released, indicating that the maximum production achieved was actually around 462.000 U/gcél.úmida. Study characterization of enzyme kinetics showed that the temperature of maximum activity is 65 °C with activation energy equal to 142.3 kJ/mol. Study of stability in solvent showed that the enzyme retains activity in the presence of 2- propanol.